The Procedure of Componential Analysis: Assessing the Literary Translation of Moroccan Cultural Terms into English - Elkhairat, Abdelghani; TAMIM, Abderrafiq (International Journal of Language and Literary Studies, 2025)
This paper examines the translation of cultural terms in ???? ??????? (lu?bat ?Nnisy?n) (1995) by the Moroccan novelist Mohamed Berrada and its English version of The Game of Forgetting translated by the Palestinian-American Issa J. Boullata (1996). The aim of this paper is to discuss the problematic aspects that translators often encounter in finding equivalent lexical terms in the target language due to cultural disparities. Componential Analysis (CA) is one of the procedures that translators and researchers opt for to solve cultural issues and objectively assess translations free from cultural constraints. On this basis, we analyse some samples from the English translation of the novel using a comparative procedure to identify semantic features and, consequently, reveal some limitations in the English translation. We conclude that in many cases the original meaning of the source language is lost or distorted, suggesting alternative translation possibilities for different cultural cases.